2020
DOI: 10.1002/cti2.1181
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells prevent overwhelming inflammation and reduce infection severity via recruiting CXCR3+ regulatory T cells

Abstract: MSCs recruit CXCR3 + Tregs to prevent infection W Li et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Mesenchymal stem cells (MSCs) hold great promise as a feasible and effective biological treatment for inflammation-related diseases [ 11 , 12 ]. MSCs have been shown to elicit immunomodulatory and tissue repair effects in lung inflammatory diseases, including reducing airway inflammation and ameliorating lung function [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) hold great promise as a feasible and effective biological treatment for inflammation-related diseases [ 11 , 12 ]. MSCs have been shown to elicit immunomodulatory and tissue repair effects in lung inflammatory diseases, including reducing airway inflammation and ameliorating lung function [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study confirmed that the promotion of Tregs arises from an epigenetic conversion of conventional T cells to Tregs rather than expansion of natural Tregs ( Azevedo et al, 2020 ). In a murine model of respiratory infection, UC-MSCs were shown to be engulfed by lung phagocytes, which then secreted C-X-C motif ligand (CXCL)9 and CXCL10, leading to the recruitment of particularly suppressive C-X-C motif receptor (CXCR)3 + Tregs ( Li et al, 2020a ). In addition to T helper cells, MSCs also significantly impair the IFN-γ production and cytotoxic activity of CTLs ( Maccario et al, 2005 ; Malcherek et al, 2014 ).…”
Section: Regulation Of Adaptive Immunity By Mscsmentioning
confidence: 99%
“…Li et al observed a significant increase in CXCR3+ Tregs in the lungs and lymphoid tissues post-MSC infusion. MSCs also increased the production of CXCL9 and CXCL10 produced by lung phagocytes which mediate the recruitment of Tregs [ 34 ].…”
Section: Mesenchymal Stem Cell Therapy To Reverse Aging Effects On the Immune Systemmentioning
confidence: 99%
“…Therefore, ex vivo expansion of MSCs and subsequent administration of optimized dosage is necessary to maintain and boost the effects of MSCs in vivo [ 32 ]. Furthermore, numerous in vivo and in vitro studies have proven that MSCs have low immunogenicity, excellent immunomodulatory function, and homing capability to regenerate damaged tissues through multipotent differentiation and paracrine secretion [ 11 , 33 , 34 , 35 , 36 ]. Despite that, the current studies are not primarily focused on aging or the restoration of the immune system.…”
Section: Introductionmentioning
confidence: 99%